Learning during emergency remote teaching in Portugal: higher education students' emotional snapshot - Cardoso, Paula (2022)
This chapter will address results of LE@D’s project “Teaching in Times of Emergency: Digital Transition,” which focused on the experience of rapid digital transition to an “emergency teaching,” a scenario quite different from distance education. Through a mixed methods approach, data was collected through an online questionnaire applied to students and videoconference interviews conducted with both higher education faculty and students. Participants in this research are students and faculty from eight Portuguese higher education institutions, four from universities (three public and one private) and four from polytechnic institutes (three public and one private), covering the regions of Lisbon and Tagus Valley, Alentejo and Algarve (Central and Southern Portugal). In this chapter, the authors present a preliminary analysis of the results obtained related to the psychological aspects experienced during this period, aiming at understanding the impact this shift has had on students’ cognitive adaptation and social and emotional processes.